CITRAAN PADA PUISI âTUHAN, KITA BEGITU DEKATâ KARYA ABDULHADI W.M.: KAJIAN STILISTIKA - Al-MaÃ¢Â€Â™ruf, Ali Imron (STILISTIKA, 2012)
CITRAAN PADA PUISI âTUHAN, KITA BEGITU DEKATâ KARYA ABDULHADI W.M.: KAJIAN STILISTIKAAli Imron Al-MaârufÂ  Â FKIP dan Program Pascasarjana Universitas Muhammadiyah SurakartaJl. Ahmad Yani Pabelan Kartasura Tromol Pos I Surakarta 57102 Telpon (0271) 717412 Ponsel: 081329107250 Pos-El: aliimron_almakruf@yahoo.com/ali_imron@ums.ac.idÂ AbstractThis study aimedÂ to:Â 1)Â describeÂ the use ofÂ imageryÂ in theÂ poem"Lord,Â WereÂ So Close" byÂ AbdulhadiÂ WM, 2)Â describe theÂ ideasimplicit inÂ the poem.Â The method usedÂ isÂ descriptiveÂ qualitativemethod.Â Data collectionÂ was done by usingÂ librariesÂ and record.Data analysis wasÂ performedÂ by the method ofÂ semioticÂ reading ofÂ the modelÂ consists ofÂ readingsÂ heuristicsÂ andÂ hermeneutics.The resultsÂ andÂ discussionÂ showÂ that:Â resultsÂ andÂ discussionÂ showÂ that:Â 1)Â theÂ poemÂ "Lord,Â WereSo Close",Â the poetÂ useÂ imageryÂ toÂ create theÂ imageryÂ onÂ the ideas presentedÂ in an interestingÂ andÂ expressive.Â ImagesÂ areusedÂ inÂ the poemÂ areÂ visualÂ imagesÂ andÂ intellectualÂ  images.Interestingly,Â theÂ poemsÂ imageryÂ showsÂ distinctivenessÂ anduniquenessÂ asÂ aÂ creativeÂ form ofÂ individuationÂ poetsÂ create new formsÂ of innovativeÂ language, 2)Â the ideaÂ isÂ implicit inÂ theÂ notion of transcendentalÂ this orÂ propheticÂ spirit expressedrelationshipÂ withÂ theÂ intimacyÂ betweenÂ Creator andÂ creature;Â 3)Â stilistikaÂ studyÂ  literatureÂ canÂ make an important contributionÂ in the analysis ofÂ literary works.Â In thatÂ studyÂ stilistikadescribeÂ the phenomenonÂ of languageÂ in literatureÂ toÂ reveal thepeculiaritiesÂ and distinctiveÂ language as a meansÂ of literaryexpressionÂ in order toÂ create the effect ofÂ a particularÂ meaningÂ in order to achieveÂ an aestheticÂ effect. Key words:Â imagery,Â the poemÂ "Lord,Â WeÂ So Close",Â the studyStilistika